THE IMPORTANCE OF CONSCIOUS USE OF ANTIBIOTICS (CIPEEX, 2025)
The discovery of penicillin transformed medicine by enablingthe effective treatment of serious infections. Over time, several classes of antibiotics emerged, each with specificmechanisms of action, such as beta-lactams, which attack thebacterial cell wall, and aminoglycosides, which interfere withthe production of essential proteins, each with specificmechanisms to combat bacteria. However, the excessive use of these drugs has led to increased bacterial resistance whenmicroorganisms become able to survive antibiotics. Thisphenomenon now poses a serious threat to public health, requiring greater awareness of the rational use of these drugs. The study aimed to emphasize the importance of the conscioususe of antibiotics, pointing out the risks of incorrect use andsuggesting strategies that promote responsible practicesamong both health professionals and the general population. A literature review was conducted in the SciELO, LILACS, andGoogle Scholar databases, including articles publishedbetween 2020 and 2024 that addressed bacterial resistance, rational use of antibiotics, and educational actions. The textswere analyzed qualitatively to identify relevant patterns andrecommendations. The analysis showed that practices such as self-medication, inappropriate treatment interruption, andunnecessary prescription are determining factors for bacterialresistance. In addition, the absence of pharmaceuticalmonitoring and the lack of adequate information compromisetherapeutic efficacy and increase health risks. It was observed that educational campaigns, professional training, and antimicrobial stewardship programs have shownpositive results in reducing the inappropriate use of antibioticsand controlling microbial resistance. It is concluded thatantimicrobial resistance is directly related to the inappropriateuse of antibiotics and represents a threat to global publichealth. The implementation of educational measures, prescription protocols, and pharmaceutical monitoring isessential to contain this problem, ensuring the effectiveness ofthese drugs for future generations.